2023
DOI: 10.1021/jacs.2c11502
|View full text |Cite
|
Sign up to set email alerts
|

Tough while Recyclable Plastics Enabled by Monothiodilactone Monomers

Abstract: The current scale of plastics production and the attendant waste disposal issues represent an underexplored opportunity for chemically recyclable polymers. Typical recyclable polymers are subject to the trade-off between the monomer's polymerizability and the polymer's depolymerizability as well as insufficient performance for practical applications. Herein, we demonstrate that a single atom oxygen-by-sulfur substitution of relatively highly strained dilactone is an effective and robust strategy for converting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
67
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 73 publications
0
67
0
Order By: Relevance
“…26,27,[35][36][37] Moving down the periodic table, sulfur containing ROCOP monomer combinations likewise exist which mostly remain to be explored in terpolymerisation reactions. 33,[38][39][40][41][42][43][44][45] Phthalic thioanhydride (PTA)/epoxide ROCOP for example yields poly[ester-alt-thioesters] while CS 2 /epoxide ROCOP can yield poly(monothio-alttrithiocarbonate) as reported by Werner and coworkers although the formal product of alternating ROCOP would be a poly(dithiocarbonate). 41,[46][47][48] Combining these ROCOPs, we recently reported a lithium catalysed PTA/CS 2 /epoxide ring-opening terpolymerisation (ROTERP, with propylene oxide (PO) or butylene oxide (BO)) and observed the formation of poly(ester-alt-ester-alttrithiocarbonates) with a few erroneous thioester links (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…26,27,[35][36][37] Moving down the periodic table, sulfur containing ROCOP monomer combinations likewise exist which mostly remain to be explored in terpolymerisation reactions. 33,[38][39][40][41][42][43][44][45] Phthalic thioanhydride (PTA)/epoxide ROCOP for example yields poly[ester-alt-thioesters] while CS 2 /epoxide ROCOP can yield poly(monothio-alttrithiocarbonate) as reported by Werner and coworkers although the formal product of alternating ROCOP would be a poly(dithiocarbonate). 41,[46][47][48] Combining these ROCOPs, we recently reported a lithium catalysed PTA/CS 2 /epoxide ring-opening terpolymerisation (ROTERP, with propylene oxide (PO) or butylene oxide (BO)) and observed the formation of poly(ester-alt-ester-alttrithiocarbonates) with a few erroneous thioester links (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The hybrid lactone/thiolactone monomer can be recycled at 120 °C under vacuum with PhSNa as the catalyst, highlighting the dilactone/dithiolactone hybrid as an effective strategy for converting "non-recyclable" polyester into a chemically recyclable polymer. [121] Notably, in both hybrid lactone/lactam and lactone/thiolactone monomers, the contrast in bond stability (amide, ester, and thioester bonds) gives rise to perfect ROP regioselectivity.…”
Section: Poly(ester-amide) and Poly(ester-thioester) From Hct/lct Dil...mentioning
confidence: 99%
“…11 These polythioesters are readily depolymerizable in the presence of a thiol functionality and a base at 25 1C 11 or in the presence of sodium thiophenolate at 60 1C. 12 The simulated biodegradation studies of poly(b-thioesters) in phosphate buffer at 40 1C have revealed the onset of degradation after 14 days, supporting their swift degradability. 13 However, the number of examples in the literature is notably limited, and the reported systems have undergone stress relaxation under mild temperature conditions, resulting in a narrow service temperature.…”
mentioning
confidence: 94%